Influence of the network modifier on the characteristics of MSnO3 (M=Sr and,Ca) thin films synthesized by chemical solution deposition - Alves, M. C. F.; Marinho, R. M. M.; Casali, G. P.; Siu-Li, M.; Deputier, S.; Guilloux-Viry, M.; Souza, A. G.; Longo, E. [UNESP]; Weber, I. T.; Santos, I. M. G.; Bouquet, V. (Elsevier B.V., 2013)
CaSnO3 and SrSnO3 alkaline earth stannate thin films were prepared by chemical solution deposition using the polymeric precursor method on various single crystal substrates (R- and C-sapphire and 100-SrTiO3) at different temperatures. The films were characterized by X-ray diffraction (theta-2 theta, omega- and (phi-scans), field emission scanning electron microscopy, atomic force microscopy, micro-Raman spectroscopy and photoluminescence. Epitaxial SrSnO3 and CaSnO3 thin films were obtained on SrTiO3 with a high crystalline quality. The long-range symmetry promoted a short-range disorder which led to photoluminescence in the epitaxial films. In contrast, the films deposited on sapphire exhibited a random polycrystalline growth with no meaningful emission regardless of the substrate orientation. The network modifier (Ca or Sr) and the substrate (sapphire or SrTiO3) influenced the crystallization process and/or the microstructure. Higher is the tilts of the SnO6 octahedra, as in CaSnO3, higher is the crystallization temperature, which changed also the nucleation/grain growth process. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Perovskite; Stannates; Chemical solution deposition; Polymeric precursor method; Epitaxial growth; Photoluminescence